Proses Transaski Jual Beli Rumah oleh Novel Home Sweet Loan karya Almira Bastari - Tias Mughnii Nur Aisyah; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the buying and selling of houses and land in the city of Jakarta in elite areas, where the average employee income is only single digits in front of millions of rupiah which influences the needs and savings of employees in the novel Home Sweet Loan by Almira Bastira. The data source is the novel Home Sweet by Almira Bastira. This type of research is descriptive qualitative. The data used is dialogue data between characters in the novel Home Sweet Loan by Almira Bastira. Data collection is carried out by reading, observing and analyzing. Some of the analytical research results presented by this author are in the big city, namely DKI Jakarta, such as the debate about buying a residential house to live in according to income which of course varies for each person, as well as the problem of getting a house to live in by considering how to buy it. in cash, mortgage, or rental to get a house, building, apartment or flat.